The harbour of Elaia: A palynological archive for human environmental interactions during the last 7500 years. (1st October 2016) - Shumilovskikh, Lyudmila S.; Seeliger, Martin; Feuser, Stefan; Novenko, Elena; Schlütz, Frank; Pint, Anna; Pirson, Felix; Brückner, Helmut
Abstract: Elaia, the harbour city for ancient Pergamon (western Turkey), was investigated using geoarchaeological methods. The rise and fall of Elaia were closely linked to the flourishing period of Pergamon, which ruled wide parts of today's western Turkey in Hellenistic times. In the framework of this research, the palynological analysis of a 9 m sediment core, Ela-70, retrieved from the enclosed harbour of the city, was carried out to reconstruct the vegetation and environmental history of the wider Gulf of Elaia region. An age-depth model, based on 11 calibrated radiocarbon ages, starting from 7.5 ka BP, provides the basis for the high resolution study of sediments from the Hellenistic period, as well as before and after. The lower part of the pollen diagram is characterised by high percentages of deciduous oaks and pines, suggesting the dominance of open forests close to the coring site. The change from oak forests to a cultural landscape, with olive, pistachio, walnut, and grape, started around 850 BC, reaching a maximum ca. 250 BC, and continuing to ca. AD 800. This period is characterised by increase of fire activity, soil erosion intensity, and pastoral farming. Such long-lasting intensive land use likely led to the climax ecosystem turnover from open deciduous oak forests to pine stands, while salt marshes developed around the coring site. The discovery of the dinoflagellate cysts of Peridinium ponticum, a Black Sea endemic species, in the harbour of Elaia evidences maritime trade between the Aegean Sea and the Black Sea; its first occurrence coincides with the time of the Mithridatic Wars (1st century BC). In conclusion, palynological data, in addition to historical and archaeological records, provide a deeper insight into human environmental interactions, as derived from the geoarchaeological archive of the harbour of Elaia.